2019
DOI: 10.1002/rmb2.12291
|View full text |Cite
|
Sign up to set email alerts
|

In vitro spermatogenesis in two‐dimensionally spread mouse testis tissues

Abstract: Purpose Mouse in vitro spermatogenesis is possible with classical organ culture methods, by placing the testis tissue at the interphase between culture medium and air. In this condition, however, a tissue piece tends to round up to be compact, whose central region suffers from shortage of nutrients and oxygen. In this study, the authors improved the culture condition by spreading each tissue thin and flat, by which they were able to get better access to the oxygen and nutrients. Methods Immature mouse testis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 17 publications
2
39
1
Order By: Relevance
“…Secondly, we applied silicone cover ceiling method, which used polydimethylsiloxane (PDMS) ceiling (PC) chip having 160 µm-depth square dent, to hold the testis tissue in the dent space making it thin and flat on the agarose gel (Fig. 2 C,D) 28 . Thirdly, we tested different concentrations of AlbuMAX from 10 to 40 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we applied silicone cover ceiling method, which used polydimethylsiloxane (PDMS) ceiling (PC) chip having 160 µm-depth square dent, to hold the testis tissue in the dent space making it thin and flat on the agarose gel (Fig. 2 C,D) 28 . Thirdly, we tested different concentrations of AlbuMAX from 10 to 40 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…In cases that PC method was applied, single tissue was placed on a gel, and PC chip having 160 μm depth of dent was covered over the tissue. The PC was prepared based on our previous papers 28 , 53 . Briefly, PDMS prepolymer and curing reagent (Silpot 184; Dow Corning) were mixed at a 10:1 weight ratio.…”
Section: Methodsmentioning
confidence: 99%
“… 63 In follow-up work in 2019, Komeya et al placed the immature mouse testis tissues on agarose gel blocks and forced them to be spread as a monolayer using a microfluidic ceiling system. They observed that the presence of the PDMS microfluidic device chip elevated the initiation and maintenance of spermatogenesis, following by increasing the number of meiotic germ cells, and enhancing the spermatogenesis up to round/elongating spermatids which were confirmed by immunohistochemical evaluation 171 ( Table 4 ).…”
Section: Microfluidic Systems For Male Reproductive Regenerationmentioning
confidence: 80%
“…Our contradictory findings may have resulted from differences in the tissue culture system (with or without an agarose gel block), culture media flow rate (0.002 mL/min [ 37 ] vs. 0.00017 mL/min in our study), or the type of device fabrication (3D printing-PDMS or a modified conventional cell culture plate). Although gonadal tissue culture on agarose gel blocks has been attempted [ 17 , 38 ], recent evidence showed a diminished distribution of GFP protein markers related to spermatid development during long-term mouse testicular tissue culture using agarose gel [ 36 ]. With more than a 10-times lower flow rate [ 37 ], the oxygen and nutrients diffused through the agarose gel and the hydrogel encapsulation might have been insufficient [ 35 ].…”
Section: Discussionmentioning
confidence: 99%